Evaluation of Acquired Knowledge about Occupational Safety in Dual Education - Ivana Tureková (UIKTEN, 2021)
In Slovakia, dual vocational education and training is based on the cooperation between secondary vocational schools and companies. Companies take full responsibility for the quality of education and training in occupational safety and knowledge of operating activities risks. In our article, we aimed to survey pupils with an attitude questionnaire about the quality and experience with safety and education at the employer`s workplace during vocational education and training. Ninety respondents, preparing for their professions in the automotive industry, participated in our survey. The analysis of the questionnaires revealed that the students could not relevantly identify the most significant dangers and risks in the workplaces to which they are exposed in the current work. An essential recommended measure is a high-quality inclusion of these topics into training using activating methods in this process and better methodological and vocational preparation for employers` lecturers.